Neutrophils in COVID-19 - Reusch, Nico; De Domenico, Elena; Bonaguro, Lorenzo; Schulte-Schrepping, Jonas; Baßler, Kevin; Schultze, Joachim L.; Aschenbrenner, Anna C. (Frontiers in Immunology, 2021)
Strong evidence has been accumulated since the beginning of the COVID-19 pandemic that neutrophils play an important role in the pathophysiology, particularly in those with severe disease courses. While originally considered to be a rather homogeneous cell type, recent attention to neutrophils has uncovered their fascinating transcriptional and functional diversity as well as their developmental trajectories. These new findings are important to better understand the many facets of neutrophil involvement not only in COVID-19 but also many other acute or chronic inflammatory diseases, both communicable and non-communicable. Here, we highlight the observed immune deviation of neutrophils in COVID-19 and summarize several promising therapeutic attempts to precisely target neutrophils and their reactivity in patients with COVID-19.